Techniques of Handling of Accounting Documents and Detection of Creative Accounting Using Foreign Models in the Conditions of the Slovak Republic - Roman BLAZEK; Pavol DURANA (Communications of International Proceedings, 2020)
This article deals with creative accounting and specific handling techniques, which are widespread throughout the world and thus in the Slovak Republic. The situation that Enron started has gradually spread around the world, as evidenced by the scandals of WorldCom, Tyco, etc. Techniques began to be used to manipulate accounting documents and records, putting companies in a better position, managers being able to meet the goals originally set by the company's management, thus enriching themselves in the form of rewards, but achieved illegally, which later stands the company name. customers or, in the worst case, the whole existence. These techniques need to be pointed out because they have a negative impact on companies, employees, customers, donors, but also on the region in which the company operates or on the state. The article also presents methods to detect this illegal activity, which can ultimately and with timely interventions can once again steer companies in the right direction, ie in a direction without manipulation. No country in the world can avoid manipulating accounting documents. People are resourceful and want their businesses to make a profit. The combination of these two aspects always exists with manipulation, so it is necessary to inform the general public about this phenomenon. The aim of the article is to reveal the current situation of using techniques for manipulating financial statements and to describe the methods of their detection.
Keywords: Creative accounting; Purposeful manipulation; Detection models; Accounting documents